2019
DOI: 10.1103/physrevb.99.174311
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical quantum phase transitions in Weyl semimetals

Abstract: The quench dynamics in type-I inversion symmetric Weyl semimetals (WSM) are explored in this work which, due to the form of the Hamiltonian, may be readily extended to two-dimensional Chern insulators. We analyze the role of equilibrium topological properties characterized by the Chern number of the pre-quench ground state in dictating the non-equilibrium dynamics of the system, specifically, the emergence of dynamical quantum phase transitions (DQPT). By investigating the ground state fidelity, it is found th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…But later it has been shown that there may not be non-analyticity in the rate function versus time plot when the quench is across the critical point or there may be a non-analyticity when the quench is not across the critical point. [44] [39] [45]. We show here that the long time limit of our rate function at the T = 0 shows non-analyticity only if the system is quenched across the critical point.…”
Section: T=0 Casementioning
confidence: 97%
“…But later it has been shown that there may not be non-analyticity in the rate function versus time plot when the quench is across the critical point or there may be a non-analyticity when the quench is not across the critical point. [44] [39] [45]. We show here that the long time limit of our rate function at the T = 0 shows non-analyticity only if the system is quenched across the critical point.…”
Section: T=0 Casementioning
confidence: 97%
“…In addition, we compare mirror-symmetry-protected DQPTs with other topologically robust DQPTs in highdimensional systems. When a system can be seen as a collection of 1D (2D) topological systems, robust DQPTs also occur because winding numbers (Chern numbers) can be defined for general lines (planes) in the BZ [37,38,50]. The band topology originates from translational symmetry.…”
Section: B Mirror-symmetry-protected Dqptsmentioning
confidence: 99%
“…Within a quantum quench, while a system is prepared as the ground state of an initial Hamiltonian, the state evolves under a different Hamiltonian with suddenly switched parameters. A dynamical quantum phase transition (DQPT) is also known as a nonequilibrium topological phenomenon induced by quantum quenches [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…and others [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. Additionally, several experiments have directly observed DQPTs, including trapped ions simulations [73][74][75][76], 53-qubit quantum simulations [77], nuclear magnetic resonance quantum simulators [78], quantum walks of photons [79,80], and spinor condensate simulations [81].…”
Section: Introductionmentioning
confidence: 99%